Constraining protoplanetary disc evolution using accretion rate and disc mass measurements: the usefulness of the dimensionless accretion parameter. Issue 2 (10th March 2017) - Rosotti, Giovanni P.; Clarke, Cathie J.; Manara, Carlo F.; Facchini, Stefano
Abstract: We explore how measurements of protoplanetary disc masses and accretion rates provided by surveys of star-forming regions can be analysed via the dimensionless accretion parameter, which we define as the product of the accretion rate and stellar age divided by the disc mass. By extending and generalizing the study of Jones et al., we demonstrate that this parameter should be less than or of order unity for a wide range of evolutionary scenarios, rising above unity only during the final stages of outside-in clearing by external photoevaporation. We use this result to assess the reliability of disc mass estimates derived from CO isotopologues and sub-mm continuum emission by examining the distribution of accretion efficiencies in regions that are not subject to external photoevaporation. We find that while dust-based mass estimates produce results compatible with theoretical expectations assuming a canonical dust-to-gas ratio, the systematically lower CO-based estimates yield accretion efficiencies significantly above unity in contrast with the theory. This finding provides additional evidence that CO-based disc masses are an underestimate, in line with arguments that have been made on the basis of chemical modelling of relatively small samples. On the other hand, we demonstrate that dust-based mass estimates are sufficiently accurate to reveal distinctly higher accretion efficiencies in the Trapezium cluster, where this result is expected, given the evident importance of external photoevaporation. We therefore propose the dimensionless accretion parameter as a new diagnostic of external photoevaporation in other star-forming regions.